2009
DOI: 10.1164/rccm.200808-1359oc
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux and Pulmonary Fibrosis in Scleroderma

Abstract: Patients with SSc with ILD have more severe reflux (i.e., more reflux episodes and more reflux reaching the proximal esophagus). Whether or not the development of ILD in patients with SSc can be prevented by reflux-reducing treatments needs to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(151 citation statements)
references
References 54 publications
7
132
1
11
Order By: Relevance
“…The prevalence defined by maximal diameter (Dmax) was consistently higher than carinal diameter (Dcar), indicating maximal diameter is more sensitive but less specific criteria for esophageal dilation. Accumulating evidence suggests an important role of esophageal dysfunction in the development of lung disease in systemic sclerosis or other lung diseases (el-Serag and Sonnenberg 1997;Tobin et al 1998;Marie et al 2001;Savarino et al 2009;Christmann et al 2010;Patiwetwitoon et al 2012). In this study, we found a correlation between esophageal parameters and pulmonary function tests in systemic sclerosis patients.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The prevalence defined by maximal diameter (Dmax) was consistently higher than carinal diameter (Dcar), indicating maximal diameter is more sensitive but less specific criteria for esophageal dilation. Accumulating evidence suggests an important role of esophageal dysfunction in the development of lung disease in systemic sclerosis or other lung diseases (el-Serag and Sonnenberg 1997;Tobin et al 1998;Marie et al 2001;Savarino et al 2009;Christmann et al 2010;Patiwetwitoon et al 2012). In this study, we found a correlation between esophageal parameters and pulmonary function tests in systemic sclerosis patients.…”
Section: Discussionsupporting
confidence: 62%
“…It has been suggested that esophageal dysfunction and aspiration may play a role in pathogenesis of interstitial lung disease in systemic sclerosis and other lung diseases (el-Serag and Sonnenberg 1997; Tobin et al 1998;Marie et al 2001;Savarino et al 2009;Christmann et al 2010). Esophageal dilation on CT scan correlates well with esophageal dysfunction (Pitrez et al 2006;Vonk et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…GERD is also frequent in patients with CTD. Studies with 24-hour pH with and without impedance monitoring demonstrated abnormal reflux in 83% to 50% (8,9,24) of patients. A negative impact of abnormal reflux in the pulmonary function has been demonstrated.…”
Section: Connective Tissue Disordersmentioning
confidence: 95%
“…Similarly, in an earlier pathophysiological study in a group of scleroderma patients with various degrees of pulmonary fibrosis based on high resolution computed tomography, not only acid but also weakly acidic refluxes were found much higher in patients with more severe than in those with mild or moderate pulmonary fibrosis. 10 In conclusion, we would like to emphasize that reflux monitoring plays a fundamental role in confirming the presence of GERD in IPF patients and, therefore, the benefit of PPI use in them should be evaluated in carefully investigated subjects in order to provide stronger evidence that PPI may be helpful for their wellbeing and survival.…”
Section: To the Editormentioning
confidence: 97%